2022
DOI: 10.1063/5.0114764
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the unsteady surface pressure fluctuation patterns over an airfoil

Abstract: This article presents a comprehensive mapping of wall pressure fluctuations over an airfoil under three different inflow conditions to shed light on some basic assumptions taken granted for the recent aeroacoustic and aerodynamics experimental studies and in the noise prediction models. Unsteady and steady pressure measurements were performed over a heavily instrumented airfoil which was exposed to smooth inflow, grid generated turbulent inflow, and a smooth inflow with a tripping tape over the airfoil to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The associated pressure fluctuations create aerodynamic imbalances around the structure and lead to additional pitching moments of aerodynamic nature. The interaction with inertial and elastic moments promotes the onset of stall-induced structural oscillations [12][13][14]. The manifestation of such oscillations is experimentally and numerically addressed in recent studies.…”
Section: Introductionmentioning
confidence: 99%
“…The associated pressure fluctuations create aerodynamic imbalances around the structure and lead to additional pitching moments of aerodynamic nature. The interaction with inertial and elastic moments promotes the onset of stall-induced structural oscillations [12][13][14]. The manifestation of such oscillations is experimentally and numerically addressed in recent studies.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the angle of attack on the turbulence interaction noise has previously been shown to be insignificant, 2 yet there is a profound change in the airfoil response function, which does not have a dramatic effect on noise generation. 3 Furthermore, Celik et al 4,5 demonstrated that the lack of sensitivity to the angle of attack extends to the lift and drag spectra too. Airfoil geometry studies in the context of turbulence interaction noise indicate that airfoil thickness and camber play important roles in noise generation.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure is a thermodynamic property that plays a key role in fluid mechanics. It is of utmost importance in aerodynamic load prediction [1,2,3], noise generation [4,5], flow instability and turbulence [6,7,8], and flow control [9]. The increase of time resolution in velocity field measurements during the last decade has opened the path to obtaining instantaneous pressure fields by combining experimental data with the flow governing equations [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, pressure distribution data is crucial for aerodynamic design optimization [19] and many surrogate models have recently been developed to reduce the computational time involved in predicting aerodynamic forces during the design process [20,21,22,23]. In the context of unsteady aerodynamics, pressure distribution data are used to provide insights on the turbulent structures responsible for the far-field noise generated by unsteady airfoils [4,24,5] and also to estimate the instant at which the flow separates near the leading edge [25,26,27]. This is particularly useful for developing control strategies for dynamic stall [28,29].…”
Section: Introductionmentioning
confidence: 99%